Índice de refração em amostras densas de átomos frios - Brambila, Felipe Carvalho (Universidade Federal de São Carlos, 2025)
Considering the study of the interaction between radiation and matter, an interesting phenomenon is refraction. This is because in most optical materials a refractive index of the order of unity is experimentally found, while classical and semi-classical theories predict extremely high indices. Recently, a study showed that the saturation of the refractive index, not predicted in the linear mean-field interaction between matter and light, lies in the strong correlation of the light emission of a dense atomic medium. However, this saturation does not have experimental evidence yet. The experimental group of which the student is part has an apparatus capable of producing cold atomic clouds of bosonic Strontium, reaching such densities that make it possible to measure this limit for the index. Given that the parameter’s space is large, a numerical guide is necessary to identify the desired effect for different mismatches and sample densities. This project is part of this context; it’s main objective being to obtain, through simulations, the refractive index as a function of the spatial density of an atomic cloud.
Refraction index of dense samples of cold atoms
Keywords: Átomos frios; Índice de refração; Modelo de Dipolos Acoplados; Efeitos coletivos no transporte de luz; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESPECTROS ATOMICOS E INTEGRACAO DE FOTONS